How Mongolia's milk-based empire got its start. (15th November 2018) - Unknown
Hunter-gatherers on Asia's eastern steppes learnt milking skills from western foreigners, DNA suggests. Hunter-gatherers on Asia's eastern steppes learnt milking skills from western foreigners, DNA suggests.